PERAWATAN MESIN BELT CONVEYOR (UNIB Press, 2024)
Abstract: Belt conveyor serves to move goods in large quantities continuously from the first end of the conveyor (initial) to the other end of the conveyor (final). The working principle of the belt conveyor consists of the main component of the machine is a belt whose working principle is to transport material to be moved from the ship unloader or from the reclaimer hopper. The physical form of the belt is a belt that extends along the conveyor. Maintenance on belt conveyor machines is carried out regularly, such as weekly maintenance and monthly maintenance on each component. This periodic maintenance is carried out starting from the damage inspection stage and the stage of replacing damaged components.Analyze and observe the belt conveyor machine by collecting data on problems that can damage the belt conveyor machine and can hinder the production process. Keywords: belt conveyor, prepentive maintenance.